2018
DOI: 10.12688/f1000research.13548.1
|View full text |Cite
|
Sign up to set email alerts
|

The physiological functions of central nervous system pericytes and a potential role in pain

Abstract: Central nervous system (CNS) pericytes regulate critical functions of the neurovascular unit in health and disease. CNS pericytes are an attractive pharmacological target for their position within the neurovasculature and for their role in neuroinflammation. Whether the function of CNS pericytes also affects pain states and nociceptive mechanisms is currently not understood. Could it be that pericytes hold the key to pain associated with CNS blood vessel dysfunction? This article reviews recent findings on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Pain is a significant function of the central nervous system [52]. In the present study, Judo 40 significantly reduced the perception of pain on posttreatment day one, indicating that activities of the CNS are affected by the insecticide, through the inhibition of pain processing in the spinal cord [53].…”
Section: Discussionsupporting
confidence: 54%
“…Pain is a significant function of the central nervous system [52]. In the present study, Judo 40 significantly reduced the perception of pain on posttreatment day one, indicating that activities of the CNS are affected by the insecticide, through the inhibition of pain processing in the spinal cord [53].…”
Section: Discussionsupporting
confidence: 54%
“…The Pericytes are mesodermal-derived cells covering the CNS capillaries to regulate vascular stability, diameter, cerebral blood flow, and extracellular membrane protein secretion [ 13 , 47 ]. The BBB ECs and their associated pericytes both produce TGF-β, which is involved in regulating the maintenance of BBB properties and possess functional TGF-β receptors [ 48 , 49 ].…”
Section: The Blood–brain-barrier (Bbb)mentioning
confidence: 99%
“…Additionally, pericytes are involved in the pathogenesis and development of various diseases. For instance, under ischemic conditions, pericytes constrict the capillaries in rigidity and hinder the flow of blood cells, which eventually prevents microcirculatory reperfusion even if the plaque has been removed in stroke disorders (Beazley-Long et al, 2018). Furthermore, studies have indicated that pericytes are associated with other neurovascular disorders, including WMI, cerebral hemorrhage, and hypoxic–ischemic brain damage (Hill et al, 2014).…”
Section: Introductionmentioning
confidence: 99%